2015
DOI: 10.1177/1460408615589430
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and histological findings of fat embolism in the vena cava

Abstract: We describe an unusual case of a post-traumatic fat embolism in the vena cava and left femoral vein identified on CT before the onset of fat embolism syndrome. The patient was successfully treated by insertion of a vena cava filter and venous thrombectomy. This is the first occurrence of early identification of a large fat embolus allowing its extraction before occurrence of severe respiratory failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Roson et al [6] reported a fat embolus in the right femoral vein increasing in size on serial imaging, prompting IVC filter placement and surgical thrombectomy. Vasconcelos et al [7] reported a large fat embolus in the left femoral vein and IVC, necessitating IVC filter placement and surgical thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roson et al [6] reported a fat embolus in the right femoral vein increasing in size on serial imaging, prompting IVC filter placement and surgical thrombectomy. Vasconcelos et al [7] reported a large fat embolus in the left femoral vein and IVC, necessitating IVC filter placement and surgical thrombectomy.…”
Section: Discussionmentioning
confidence: 99%
“…It is rare, however, to encounter venous fat at the site of trauma on imaging. In our literature search we encountered only ten case reports of fat emboli in the venous system detected on computed tomography (CT) imaging to date, including one in the inferior vena cava (IVC) ( Table 1 ) [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] . Note that symptoms and signs and even imaging findings of fat emboli are often difficult to distinguish from those of concurrent trauma.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of macroscopic fat emboli in the systemic veins or pulmonary arteries through computed tomography (CT) is even rarer with only a few cases published, [2][3][4][5][6][7][8] to the authors' knowledge.…”
mentioning
confidence: 99%
“…2,3,6,8 The detection of fat emboli in the cerebral arterial circulation has also been reported as the 'hypodense artery sign'.…”
mentioning
confidence: 99%
See 1 more Smart Citation